Protection-free synthesis of glycosyl dithiocarbamates in aqueous media by using 2-chloroimidazolinium reagent. Issue 31 (3rd August 2016) - Li, Gefei; Noguchi, Masato; Kashiwagura, Haruka; Tanaka, Yuuki; Serizawa, Kazunari; Shoda, Shin-ichiro
Graphical abstract: Highlights: One-step synthesis of glycosyl dithiocarbamate is possible. No protecting groups are needed. The reaction proceeds in an aqueous media. Abstract: Glycosyl dithiocarbamates (GDTCs) have been synthesized directly from the corresponding unprotected sugars and dithiocarbamate salts in good yields by using 2-chloro-1, 3-dimethylimidazolinium chloride (DMC) as condensing agent in aqueous media. The three-component one-pot synthesis of GDTCs starting from unprotected sugars, carbon disulfide, and secondary amines has also been successfully demonstrated. This is the first report on the direct synthesis of GDTCs from unprotected sugars without using any protecting groups.